Learning Habits of Students in the PGMI Department, Faculty of Tarbiyah and Teacher Training, UIN Sunan Gunung Djati Bandung - Mangkuwibawa, Hilman; Salahudin, Anas; Ginanjar, Ani Yanti (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2024)
This study aims to analyze the learning habits of students of the Elementary Madrasah Teacher Education (PGMI) Study Program, Faculty of Tarbiyah and Teacher Training, UIN Sunan Gunung Djati Bandung, including: (1) the level of students' learning habits in general, (2) the lowest learning habit indicators, and (3) the highest learning habit indicators. This study uses a descriptive quantitative approach with an analytical descriptive method. The study population was all PGMI students of the 2015/2016 intake, totaling 75 people, who were also used as samples using a total sampling technique, because the population was less than 100. Data were collected through observation, a learning habit scale questionnaire, and documentation studies. The research instrument was compiled based on six main indicators of learning habits, namely accuracy in completing academic assignments, regularity in study time, task implementation, effective learning, work efficiency, and learning technique skills. Data were analyzed using descriptive statistics through the calculation of the average (mean) with the help of the SPSS program, as well as logical analysis to support its qualitative interpretation. The results of the study show that the learning habits of PGMI students are generally in the sufficient category. The lowest indicator of study habits was work efficiency, while the highest indicator was study technique skills, which were categorized as good. These findings indicate that although students possess adequate study skills, improvements in the efficiency of managing study time and energy are still needed to optimize academic achievement.